2022
DOI: 10.1007/s00520-021-06667-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the oncologic activities (diagnosis, treatment, clinical trials enrollment) of a general hospital in a district with high prevalence of SARS-COV-2 in Italy

Abstract: Purpose Little is known about the real impact of the COVID-19 outbreak on the qualitative and quantitative fall-out on the management of cancer patients. Our objective was to provide evidence of the effects of SARS-COV-2 on the management of cancer patients in the real world. Methods In a general hospital in a district in Italy with high prevalence of COVID-19 during the first wave, we retrospectively analyzed the data of oncologic activity, namely new can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In addition, several studies demonstrated a reduction in National Cancer Institute (NCI)-sponsored cancer trials along with overall clinical trial enrollment 43 . Similar reductions in cancer clinical trials were noted worldwide, as one Italian Center saw an 84.5% reduction in patient clinical trial enrollment 42 .…”
Section: Section 2: the Impact On Research And Cancer-related Therapy...supporting
confidence: 55%
See 1 more Smart Citation
“…In addition, several studies demonstrated a reduction in National Cancer Institute (NCI)-sponsored cancer trials along with overall clinical trial enrollment 43 . Similar reductions in cancer clinical trials were noted worldwide, as one Italian Center saw an 84.5% reduction in patient clinical trial enrollment 42 .…”
Section: Section 2: the Impact On Research And Cancer-related Therapy...supporting
confidence: 55%
“…The COVID-19 pandemic drastically disrupted the conduct and management of cancer patients enrolled in clinical trials. With the onset of the pandemic, centers observed an apparent decline in the numbers of new cancer diagnoses, likely reflecting access to care issues and patient avoidance of care for fear of contracting COVID-19 42 . In addition, several studies demonstrated a reduction in National Cancer Institute (NCI)-sponsored cancer trials along with overall clinical trial enrollment 43 .…”
Section: Section 2: the Impact On Research And Cancer-related Therapy...mentioning
confidence: 99%
“…Unfortunately, the “hydroxychloroquine affair” clearly demonstrated the non‐negligible limitations of this approach in terms of ethics and scientific integrity 80,81 . Priority in healthcare is still given to patients infected with the pandemic microbe, at the expense of everyone else, even when, as seen here, various clinicians and researchers highlight the possible, or even probable, deleterious consequences of this approach in the medium and long term 1,54,82 . The prohibition of visits to hospitalized relatives imposed by national or regional policies and administrations would undoubtedly be repeated, even at the expense of definitively destroying the relationship of trust between oncologists and the family of the cancer patient that is so essential for effective medical practice 83 .…”
Section: Resultsmentioning
confidence: 95%
“…80,81 Priority in healthcare is still given to patients infected with the pandemic microbe, at the expense of everyone else, even when, as seen here, various clinicians and researchers highlight the possible, or even probable, deleterious consequences of this approach in the medium and long term. 1,54,82 The prohibition of visits to hospitalized relatives imposed by national or regional policies and administrations would undoubtedly be repeated, even at the expense of definitively destroying the relationship of trust between oncologists and the family of the cancer patient that is so essential for effective medical practice. 83 The outcome might be an unsatisfactory quality of life (i.e., happiness) and/or survival rate for cancer patients, as we are currently seeing.…”
Section: Scenariomentioning
confidence: 99%
“…The containment measures to halt the spread of the COVID-19 infection, the conversion of many oncology in-patient clinics into COVID-19 units (particularly during the first wave of the pandemic and in the regions of northern Italy), the shortage of oncologists and radiotherapists diverted to COVID-19 care, and the lack of ICU beds, occupied by patients with severe acute respiratory syndrome, have contributed significantly to this scenario, albeit with substantial differences between regions. [13][14][15] The consequences of the serious interruption of all aspects of the cancer care continuum, from screening to treatment, will potentially result in an increase in advanced-stage cancer diagnoses in the coming years and may lead to an increase in cancerrelated mortality. 16 Social isolation and anxiety due to delayed (or impeded) access to diagnosis, surgery, or systemic treatments have also affected mental well-being of patients with cancer, their caregivers, and cancer survivors.…”
Section: The Impact Of the Covid-19 Pandemic In Italymentioning
confidence: 99%